2017
DOI: 10.1039/c7ra06514k
|View full text |Cite
|
Sign up to set email alerts
|

Water soluble Ru(ii)–arene complexes of the antidiabetic drug metformin: DNA and protein binding, molecular docking, cytotoxicity and apoptosis-inducing activity

Abstract: The incorporation of antidiabetic drug metformin with organometallic Ru(arene) pharmacophore is a promising approach to develop new anticancer agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 74 publications
(67 reference statements)
2
24
0
2
Order By: Relevance
“…The observed K b values are varied as 1 (4.9 × 10 3 ) < 2 (7.1 × 10 3 M −1 ), which is in conformity with the observed trend in hypochromism (, Table ). It has been found that the order of K b values are similar with those of Ru(II)‐ p ‐cymene complexes incorporating with non‐intercalating ligands namely, [Ru( η 6 ‐ p ‐cymene)(metformin)Cl](PF 6 ) ( K b , 1.7 × 10 3 M −1 ) and [Ru( η 6 ‐ p ‐cymene)(L)Cl](PF 6 ), where L is N ‐methylhomopiperazine ( K b , 8.0 × 10 3 M −1 ) . However, on account of restricted rotation of pyrenyl groups around –N=CH groups, the partial intercalation of pyrenyl rings in complex 2 in between DNA base pairs cannot be ruled out.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The observed K b values are varied as 1 (4.9 × 10 3 ) < 2 (7.1 × 10 3 M −1 ), which is in conformity with the observed trend in hypochromism (, Table ). It has been found that the order of K b values are similar with those of Ru(II)‐ p ‐cymene complexes incorporating with non‐intercalating ligands namely, [Ru( η 6 ‐ p ‐cymene)(metformin)Cl](PF 6 ) ( K b , 1.7 × 10 3 M −1 ) and [Ru( η 6 ‐ p ‐cymene)(L)Cl](PF 6 ), where L is N ‐methylhomopiperazine ( K b , 8.0 × 10 3 M −1 ) . However, on account of restricted rotation of pyrenyl groups around –N=CH groups, the partial intercalation of pyrenyl rings in complex 2 in between DNA base pairs cannot be ruled out.…”
Section: Resultsmentioning
confidence: 79%
“…have correlated the DNA and protein binding properties of Ru(II)‐ p ‐cymene complexes with cytotoxicity and apoptosis inducing activity . We have recently reported In vitro anticancer activity of water soluble Ru‐arene complexes bearing with the antidiabetic drug metformin against cancer cells . In the regard of catalytic applications, [Ru( η 6 ‐ p‐ cymene)(κ 2 ‐ N , N ‐dmbpy)Cl] + , where dmbpy is 4,4′‐dimethyl‐2,2′‐bipyridine is reported for its catalytic transfer hydrogenation of different ketones to the corresponding alcohols .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that vanadyl complex with metformin shows potential synergistic insulin mimics, while platinum (IV) complex reveals antitumor activity . The interaction of Metformin with calf thymus DNA has been investigated by Nahid Shahabadi et al Recently DNA binding studies of water soluble ruthenium (II)‐arene complex with metformin hydrochloride (Met) as ligand have been studied …”
Section: Introductionmentioning
confidence: 99%
“…[16] The interaction of Metformin with calf thymus DNA has been investigated by Nahid Shahabadi et al [17] Recently DNA binding studies of water soluble ruthenium (II)-arene complex with metformin hydrochloride (Met) as ligand have been studied. [18] Metformin and its ternary complexes have received less attention in spite of their potential metal binding properties and promising applications. From our laboratories, we recently reported the synthesis, characterization and DNA binding studies of cobalt (II), copper (II) and oxovanadium (IV) complexes containing metformin as primary ligand and α-diimine/α-diamine as auxiliary ligands.…”
Section: Introductionmentioning
confidence: 99%